Anamnese à brasileira: epistemes, memórias e perspectivas curatoriais dissensuais no consumo de artes visuais - Scudeller, Pedro de Assis Pereira (2024)
This paper analyzes the relationship between communication and consumption in the visual arts. The work aims to conduct a cartographic and listening exercise to identify the main issues proposed by poetics and curatorships in the creative materialities of artworks and exhibitions. This is based on the observation of the phenomenon of proliferation of exhibition events in art institutions in São Paulo, which focus on historical revisions from dissensual epistemological perspectives, making some crossings and highlighting intersections. The theoretical and epistemological foundations of this research are based on the notions of the imbrication between aesthetics and politics proposed by Jacques Rancière, in his teachings on dissent (RANCIÈRE, 1996), and in his concept of sharing the sensible (RANCIÈRE, 2009), notably relating it to politicality (ROCHA, 2012), in order to observe the dissensual possibilities of other epistemes: we discuss narratives related to great collective traumatic experiences, such as slavery and coloniality, issues which are worked on, by the artist subjects, from elements of identity and their embodied experience. Throughout the work, there is an epistemological identification with the decolonial perspective, so that the narratives we are talking about, as a rule, implicitly or explicitly seek to break away from the colonial matrix of power (QUIJANO, 2000). Next, we will discuss memory and mnemonic operations as potential tools for political action, particularly in challenging hegemonic historical narratives that exclude alternative perspectives from official history. Memory serves as a powerful catalyst for the emergence of alternative narratives, which, in the context of this work, are materialized in works of art and exhibitions. To identify the art exhibitions analyzed in this research, we utilized a methodological proposal based on cartography as conceived by Suely Rolnik (1987). We combined this with Tina M. Campt's (2017) concept of listening to images to propose a compositional exercise that analyzes objects from a collective, plural perspective. This approach rejects a hermetic classification that purports to be universal. We examined exhibitions held at various institutions, including the Assis Chateaubriand Art Museum of São Paulo - MASP, the Pinacoteca of the State of São Paulo, the Paulista Museum of the University of São Paulo - Ipiranga Museum, the Dos Brasis exhibit at SESC Belenzinho, and the 34th and 35th São Paulo Biennials. The intersections of curatorial practices in these institutions reveal significant resonances in terms of historical revision dynamics, particularly in three aspects: (1) in the context of the debate on representations and Brazilian national symbols from a decolonial perspective; (2) sex-generic and intersectional issues, in response to the systemic erasure and violence suffered by these subjects; and (3) ethnic and racial issues, and the processes of healing collective traumas from political and aesthetic practices that start from peripheral and diasporic epistemologies.